Genome-Wide Association Studies (GWAS) Deliver Big Breakthroughs in Identifying Type 2 Diabetes Susceptibility Genes in the General Population - Cui, MD, Wei; Zhang, MD, PhD, Cuilin; Song, MD, ScD, Yiqing (North American Journal of Medicine and Science, 2009)
A striking epidemic of type 2 diabetes mellitus (T2D) is a major public health problem worldwide. Current medical therapies can mitigate this disorder, but rarely provide a cure, leaving patients exposed to many debilitating and life-threatening complications. Although T2D is a multifactorial disease that involves interactions between many genetic and environmental factors, genetics is believed to play an important part in the development of T2D. Linkage analyses have identified several specific gene loci in a handful of families with diabetes that segregates as an autosomal dominant trait termed maturity-onset diabetes of the young (MODY-1,-2,-3,-4,-5, -6). But for the common (>95%) form of T2D in the general population, much remains unknown about its genetic determinants.